Relationship orientation of supplier-manufacturer and sourcing project success: Partial least squares analysis - Hassan, Mohamad Ghozali; Abdul Talib, Asmat Nizam; Razalli, Mohd Rizal; Harun, Noor Aziani (2012)
The purpose of the current study was to investigate the relationship between relational-oriented exchange and outsourcing success of supplier-manufacturer relationship within Malaysia.This study used the partial least squares (PLS) and structural equation modeling (SEM) tool to test the hypotheses.The data was gathered from a postal survey of 865 electrical & electronics sub-sector, of which 216 respondents participated in this study.The result indicated that relational-oriented exchange was positively related to the outsourcing success. Implications of the findings are further elaborated.